Oncological outcome of primary non‐metastatic soft tissue sarcoma treated by neoadjuvant isolated limb perfusion and tumor resection. Issue 8 (12th March 2014) - Jakob, Jens; Tunn, Per‐Ulf; Hayes, Andrew J.; Pilz, Lothar R.; Nowak, Kai; Hohenberger, Peter
Abstract Background Isolated limb perfusion (ILP) is an effective limb salvage strategy in patients with advanced soft tissue sarcoma (STS) where surgery alone would result in significant functional morbidity or mandate an amputation. Most previous reports of patients undergoing ILP focus on limb salvage rates rather than local and distant relapse rates. Here, we report the oncological outcome of sarcoma patients treated by ILP and surgery. Methods Data were retrieved from prospective ILP databases from two ILP centers following similar ILP techniques and surgical approaches. Only patients with primary, intermediate, or high grade non‐metastatic STS were included. Results The cohort comprised 90 patients. Median follow‐up was 39 months (range 3–165 months). Median tumor size was 11 cm (range 5–34). Twenty of 90 (22%) patients underwent prior debulking surgery outside the centers. Twenty‐nine of 90 (32%) had postoperative irradiation. Four of 90 underwent amputation either related to local recurrence or irresectability, 4 of 90 underwent amputation for treatment‐related complications. Fifteen of 83 (18%) patients had local recurrences after ILP and limb sparing surgery, 39 of 90 (43%) developed metastatic disease. Twenty‐two of 90 (24%) died of disease. Conclusion Preoperative ILP and tumor resection resulted in good local control in a cohort of high‐risk STS patients. J. Surg. Oncol. 2014 109:786–790. © 2014 Wiley Periodicals, Inc.